Size-controlled flow synthesis of gold nanoparticles using a segmented flow microfluidic platform - Cabeza, Victor Sebastian; Kuhn, Simon; Kulkarni, Amol A.; Jensen, Klavs F. (Langmuir, 2012)
Segmented flow is often used in the synthesis of nanomaterials to achieve narrow particle size distribution. The narrowness of the distribution is commonly attributed to the reduced dispersion associated with segmented flows. On the basis of the analysis of flow fields and the resulting particle size distribution, we demonstrate that it is the slip velocity between the two fluids and internal mixing in the continuous-phase slugs that govern the nature of the particle size distribution. The reduction in the axial dispersion has less impact on particle growth and hence on the particle size distribution. Synthesis of gold nanoparticles from HAuCl4 with rapid reduction by NaBH4 serves as a model system. Rapid reduction yields gold nuclei, which grow by agglomeration, and it is controlled by the interaction of the nuclei with local flow. Thus, the difference in the physical properties of the two phases and the inlet flow rates ultimately control the particle growth. Hence, a careful choice of continuous and dispersed phases is necessary to control the nanoparticle size and size distribution.

Insights in the diffusion controlled interfacial flow synthesis of Au nanostructures in a microfluidic system - Kulkarni, Amol A.; Cabeza, Victor Sebastian (Langmuir, 2017)
Continuous segmented flow interfacial synthesis of Au nanostructures is demonstrated in a microchannel reactor. This study brings new insights into the growth of nanostructures at continuous interfaces. The size as well as the shape of the nanostructures showed significant dependence on the reactant concentrations, reaction time, temperature, and surface tension, which actually controlled the interfacial mass transfer. The microchannel reactor assisted in achieving a high interfacial area, as well as uniformity in mass transfer effects. Hexagonal nanostructures were seen to be formed in synthesis times as short as 10 min. The wettability of the channel showed significant effect on the particle size as well as the actual shape. The hydrophobic channel yielded hexagonal structures of relatively smaller size than the hydrophilic microchannel, which yielded sharp hexagonal bipyramidal particles (diagonal distance of 30 nm). The evolution of particle size and shape for the case of hydrophilic microchannel is also shown as a function of the residence time. The interfacial synthesis approach based on a stable segmented flow promoted an excellent control on the reaction extent, reduction in axial dispersion as well as the particle size distribution.